(untitled) (La U Investiga, 2018)
The disability people have a high degree of vulnerability to different daily processes. In this investigation, the implementation of a technical aid based on the model of the “Upsee”, harness, in order to facilitate the transfer and training of the child’s progress. The methodology used was of a descriptive and non - experimental type, with a quali - quantitative and longitudinal cut approach, since after 10 months the gross motor functional measure (GMFM) level in the child was re - evaluated. A load and march support harness was made based on the child’s motor condition, in addition to the postural analysis and overload of his informal caregiver according to the Zarit index. In the child, an ectomorphic condition was identified, ranges of articular movement preserved, grade 3 muscle strength average and with initial GMFM of 46.5% and final of 58.9% with improvement observed. The evaluation of the informal primary caregiver indicated inadequate body alignmentsand a slight level of overload according to the Zarit scale. The initial evaluation guided the design and construction of the personalized harness for the patient, adapting a main support in scapular waist and shoulders; The bipolar bases of the original design are also removed due to the motor control of the lower limbs that the child possesses. The use of the harness shows changes in the level of GMFM, with an improvement in all the sections, mainly in the bipedal tasks.